Proceedings of the SmartCity360 2016 2017
DOI: 10.4108/eai.14-2-2017.152420
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Space in Cities Respecting Requirements of Specific Target Groups as Objective of Smart City Concepts

Abstract: Perception of smart city concept from the point of view of the quality of space in cities has been analysed in relation to specific target groups within urban population. There are the needs of specific target groups that have to be taken into account in the concept of smart city. To the specific target groups belong mainly children and young people (including persons accompanying them), senior people, persons with physical disabilities, persons with sensual disabilities (blind and partially sighted, deaf), pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Other studies include an impact analysis of heritage buildings in terms of socio and spatial impacts [113], a study on adaptation of autonomy systems for future smart cities for the automation of the hierarchy of needs [114] and a study on user satisfaction related to indoor spaces for terminal buildings [115]. Studies focused on the future and sharing a vision for the future were also found, which included application of interactive technologies to public spaces to influence human behavior [116], an analysis of new concepts such as running multiple businesses in the same space [117] and gathering opinions from specific target groups about smart city concepts [118].…”
Section: City Servicesmentioning
confidence: 99%
“…Other studies include an impact analysis of heritage buildings in terms of socio and spatial impacts [113], a study on adaptation of autonomy systems for future smart cities for the automation of the hierarchy of needs [114] and a study on user satisfaction related to indoor spaces for terminal buildings [115]. Studies focused on the future and sharing a vision for the future were also found, which included application of interactive technologies to public spaces to influence human behavior [116], an analysis of new concepts such as running multiple businesses in the same space [117] and gathering opinions from specific target groups about smart city concepts [118].…”
Section: City Servicesmentioning
confidence: 99%